Blanchland, a short history - Addleshaw, G. W. O (Blanchland Church & Post Office, 1951)
Keywords: blanchland

Cuckney Church and Castle - Barley, Maurice Willmore (Transactions of the Thoroton Society of Nottinghamshire, 1951)
Keywords: cuckney

The Third Abbot of Dryburgh - Bulloch, J.P.B. (Records of the Scottish Church History Society, 1951)
Keywords: dryburgh

The White Canons in England - Colvin, H.M. (Clarendon Press, 1951)
The history of the Premonstratensian order.
Keywords: 🇬🇧 great britain (general)

A repertoire of students at the College of Premontre in mediaeval Paris. - John, James J. (University of Notre Dame, 1951)
Keywords: paris (college)

Parishes: Wappenbury and Eathorpe - Salzman, L.F. (A History of the County of Warwick, 1951)
Keywords: wappenbury